Fabricación artesanaly semi-artesanal de bloques nutricionales - Tobía-Rivero, Carlos (Universidad de Costa Rica, 2013)
Farm and semi-industrial production of nutritional blocks. Due to the great interest among beef producers for improving productivity and reproductive performance, as well as facing the problems of feeding their livestock during the critical periods. The present work describes a simple way to produce nutritional blocks in farm and semi-industrial form. The blocks are described according to the objective of the producer, the profit of this supplementation type, as well as the feedstuffs and procedures in the production of the blocks. Several formulations of possible nutritional blocks are presented, varying the type and the proportion of feedstuffs.